2020
DOI: 10.1002/jlb.4ma0620-526rr
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate binding proteins contained in the murine chromosome 3 are important to control mycobacterial infection

Abstract: Guanylate binding proteins (GBPs) are important effector molecules of autonomous response induced by proinflammatory stimuli, mainly IFNs. The murine GBPs clustered in chromosome 3 (GBPchr3) contains the majority of human homologous GBPs. Despite intense efforts, mycobacterial-promoted diseases are still a major public health problem. However, the combined importance of GBPchr3 during mycobacterial infection has been overlooked. This study addresses the influence of the GBPchr3 in host immunity against mycobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 42 publications
3
22
2
Order By: Relevance
“…Understanding the immune mechanisms that restrict the intracellular growth of Mtb is essential for the rational design of interventions. Initial observations demonstrating a role for GBPs in the control of BCG growth suggested that this pathway might represent an important component of IFNg -mediated immunity to Mtb (22,23). However, while we were able detect the previously-described role for the chromosome 3 GBPs in immunity to BCG, we found that these proteins have no effect during Mtb infection.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Understanding the immune mechanisms that restrict the intracellular growth of Mtb is essential for the rational design of interventions. Initial observations demonstrating a role for GBPs in the control of BCG growth suggested that this pathway might represent an important component of IFNg -mediated immunity to Mtb (22,23). However, while we were able detect the previously-described role for the chromosome 3 GBPs in immunity to BCG, we found that these proteins have no effect during Mtb infection.…”
Section: Discussioncontrasting
confidence: 91%
“…The increased susceptibility of IFNgR -/compared to Gbp chr3-/mice indicated that the function of these GBPs accounted for some but not all of the protective effect of IFNg. Together these data show that the GBPs on chromosome 3 are able to restrict the growth of BCG in IFNg -stimulated macrophages and in the intact animal, which is consistent with the previously described roles of GBPs in immunity to BCG (22,23).…”
Section: Mycobacterium Bovis Bcg Growth Is Restricted By the Chromososupporting
confidence: 91%
See 1 more Smart Citation
“…BCG was grown in Middlebrook 7H9 broth that contained 0.05% Tween 80 and 0.2% glycerol and was supplemented with 10% albumin-dextrose-catalase. Cultures were harvested by centrifugation at the mid-exponential phase, suspended in saline containing 0.05% Tween 80, and stored at − 80 °C until use 90 .…”
Section: Methodsmentioning
confidence: 99%
“…At day seven in culture, the cells had completely differentiated into macrophages. Macrophages were seeded in 6-well plates (5 × 10 5 cells/well), 24-well plates (2 × 10 5 cells/well) or 96-well plates (1 × 10 5 cells/well) and used for in vitro studies as previously described 90 .…”
Section: Methodsmentioning
confidence: 99%